USER INTERFACE DESIGN OF E-COMMERCE WEBSITES FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN THE CULINARY INDUSTRY - Malisa Putri; M. Bagastya Rasyid; Jihan Salsabila; Muhammad Riski Saputra; Syahrul Isyam; Oki Wibowo; Miftahul Jannah (Ninety Media Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a strategic role in supporting economic growth, increasing employment opportunities, and strengthening local economies. However, many culinary MSMEs still experience challenges in adopting digital technology, including limited digital literacy, inadequate technological infrastructure, and manual sales and transaction management. These limitations hinder market expansion and reduce operational efficiency, making digital transformation increasingly necessary. This study aims to design a responsive and user-friendly user interface for a web-based e-commerce platform specifically intended for culinary MSMEs. The research method involved requirement analysis through observation, literature review, user needs identification, product data collection, order workflow analysis, and transaction management analysis. The interface design process was carried out using Figma to develop a prototype representing the overall system workflow, including customer and administrator interactions. The resulting design includes several key features such as the home page, login and registration page, product menu, payment system, order history, best seller recommendations, contact information, and logout functionality, as well as administrative features for product and transaction management. Black Box Testing was conducted to evaluate the functionality of each feature and ensure compliance with system requirements. The testing results demonstrated that all system functionalities operated successfully and consistently according to expected outcomes. The developed interface design is expected to support culinary MSMEs in improving digital marketing activities, simplifying transaction management, and increasing operational efficiency. Therefore, the proposed web-based e-commerce interface has strong potential to support the digital transformation and sustainability of culinary MSMEs in Indonesia.